Bloch-Siegert B1+- mapping for human cardiac 31P-MRS at 7 Tesla - Clarke, W; Robson, M; Rodgers, C (Wiley, 2015)
Purpose: Phosphorus MR spectroscopy (31P-MRS) is a powerful tool for investigating tissue energetics in vivo. Cardiac 31P-MRS is typically performed using surface coils that create an inhomogeneous excitation field across the myocardium. Accurate measurements of B1+ (and hence flip angle) are necessary for quantitative analysis of 31P-MR spectra. We demonstrate a Bloch-Siegert B1+-mapping method for this purpose. Theory and Methods: We compare acquisition strategies for Bloch-Siegert B1+-mapping when there are several spectral peaks. We optimize a Bloch-Siegert sensitizing (Fermi) pulse for cardiac 31P-MRS at 7T and apply it in a 3D chemical shift imaging sequence. We validate this in phantoms and skeletal muscle (against a dual-TR method) and present the first cardiac 31P B1+ -maps at 7T. Results: The Bloch-Siegert method correlates strongly (Pearson’s r = 0.90 and 0.84) and has bias <25Hz compared to a multi-TR method in phantoms and dual-TR method in muscle. Cardiac 3D B1+ -maps were measured in five normal volunteers. B1 maps based on phosphocreatine and alpha-adenosinetriphosphate correlated strongly (r=0.62), confirming that the method is T1 insensitive. Conclusion: 3D 31P Bloch-Siegert B1+ -mapping is consistent with reference methods in phantoms and skeletal muscle. It is the first method appropriate for 31P B1+-mapping in the human heart at 7T.